Postoperative analysis of a free fibular graft due to bone failure caused by a metatarsal bone tumor - Padão, Diego Loureiro; Sartori, Júlio César; Krasilchik, Lucas Ribeiro (Scientific Journal of the Foot & Ankle, 2019)
Objective: To evaluate the postoperative clinical outcomes of patients undergoing fibular grafting due to bone loss caused by metatarsal tumors. Methods: This retrospective cross-sectional study was conducted between January 2010 and December 2018 with three patients who were treated with a free fibular graft after bone loss due to metatarsal tumor resection. The patients underwent surgery with a dorsal longitudinal incision over the tumor lesion for subsequent tumor resection. The fibular graft was harvested from the distal third of the ipsilateral leg. The graft was fixed using Kirschner wires and a mini-fragment plate and cortical screws. An analysis of the patients’ ages, sex, tumor types, need for adjuvant or neoadjuvant therapy and postoperative complications was conducted. Results: All three patients who were subjected to fibular grafting for metatarsal replacement were female (100%), with a mean age of 10.3 years (± 0.61). The type of tumor found in the three patients (100%) was an aneurysmal cyst, and only the affected metatarsal showed changes. None of the patients required adjuvant or neoadjuvant therapy. Regarding the postoperative complications, two patients (66.6%) presented pseudoarthrosis, and one did not present any complications. Conclusion: Free fibular grafting is a viable option for the treatment of bone loss caused by metatarsal tumors. Level of Evidence IV, Therapeutic Studies; Case Series.